Eventration of Diaphragm or Pseudo Pleural Effusion? - MoinAzad Tehrani, M; Khoshkar, A; Agin, Kh (International Journal of Medical Toxicology and Forensic Medicine, 2013)
Background: Physicians frequently encounter chest-x ray reports of pleural effusion in patients. Thoracocentesis is the second step to diagnosis, but if there isn’t any effusion actually, thoracocentesis may lead to complication. Case Report: A 47-year-old man with a history of dyspnea and dry cough and posteroanterior (PA) chest x-ray (and right lateral decubitus) report of pleural effusion referred for thoracocentesis, but vesicular sounds at over the lungs were normal. Spiral lung CT scan revealed localized eventration of diaphragm. Conclusion: Localized eventration of right diaphragm may cause the appearance of pleural effusion in PA and also right lateral decubitus chest x-ray.